Numerical Analysis of the Influence of Bamboo Chips Variations on Road Embankment Stability and Settlement - Arasi Arahman; Dian Purnamawati Solin; Karina Meilawati Eka Putri (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2025)
Soft soil is characterized by low bearing capacity, high compressibility, and substantial settlement, thereby frequently causing complications in road embankment construction. One viable method for soil improvement is stabilization utilizing eco-friendly materials, such as bamboo chips. However, research concerning the effects of varying bamboo chip mixtures on the stability and settlement of embankments constructed on soft soil remains limited. This study aims to analyze the impact of bamboo chip mixture variations on consolidation characteristics, embankment stability, and soft soil settlement, utilizing the finite element method via PLAXIS 2D software. The investigation was conducted through one-dimensional consolidation testing (oedometer tests) on native soil and bamboo chip mixture variations of 25%, 30%, and 35%. The experimental results served as input parameters for the PLAXIS 2D numerical modeling to evaluate the safety factor and embankment settlement. The findings indicate that the incorporation of bamboo chips effectively enhances embankment stability and mitigates soil settlement compared to untreated soil conditions. The TA + BC (Native Soil + Bamboo Chips) 30% variation yielded the most optimal outcomes, exhibiting the lowest compression index and consolidation settlement, alongside a higher safety factor relative to the other variations. Overall, bamboo chips demonstrate significant potential as an economical and environmentally sustainable alternative stabilization material for road embankment construction over soft soils.